Hubungan Dukungan Keluarga dengan Pelaksanaan Pemberantasan Sarang Nyamuk di Wilayah Kerja Puskesmas Kedungmundu - Rikza Azri Musyfiq; Moch Aspihan; Iskim Luthfa (Journal of Medical Practice and Research, 2025)
Dengue Hemorrhagic Fever (DHF) remains a serious public health problem in Indonesia, with morbidity and mortality rates continuing to rise. The main prevention effort is carried out through mosquito breeding site elimination (MBSE) using the 3M Plus method, the implementation of which is highly dependent on the role of the family as the smallest unit of society. Family support plays an important role in shaping the awareness, motivation, and consistency of family members in implementing PSN on an ongoing basis. This study aims to analyze the relationship between family support and the implementation of PSN in the working area of the Kedungmundu Community Health Center. The study used a correlative analytical design with a cross-sectional approach. The sample consisted of 66 respondents selected using consecutive sampling. Data collection was conducted using a family support questionnaire and a PSN implementation questionnaire. Bivariate analysis used Sommers' d test with a significance level of 0.05. The results showed that some respondents had low family support (37.9%) and PSN implementation was in the poor category (40.9%). Sommers' d test produced a p-value of 0.000 and a correlation coefficient of r = 0.628, indicating a significant, strong, and positive relationship between family support and PSN implementation. The better the family support, the more optimal the PSN implementation.